Autonomous Ultrasonic Indoor Tracking System - Junhui Zhao; Yongcai Wang (2008 IEEE International Symposium on Parallel and Distributed Processing with Applications, 2008)
This paper proposes the autonomous ultrasonic indoor tracking system (AUITS), an ultrasound based system for locating and tracking mobile objects inside a building. Ultrasound shows promise to be exploited for a practical indoor location system due to its high accuracy ranging, low cost, safety, and imperceptibility. However, conventional ultrasonic location systems pose such challenges as high installation cost and manual calibration. The key idea of AUITS is to use only one autonomous device, positioning on one device (POD), to not only process signal acquisition but also conduct position computation. Structural topology is designed to make POD easily deployed and easily calibrated. In addition, a structural localization algorithm is proposed to provide an effective and affordable algorithm for POD to calculate the object's position. We describe the of AUITS and evaluate its performance both experimentally and with simulation. The results show that the coverage area of a POD can reach 65 m 2 and the positioning error is less than 15 cm with over 90% probability.